2017
DOI: 10.1021/acsbiomaterials.7b00642
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Glycopolymers with Assemblies of Peptide Amphiphiles via Dynamic Covalent Bonding

Abstract: In this work, peptide amphiphile (PA) with benzoboroxole (BOB) group at the hydrophilic end was prepared and assembled into fibers (PAA) with BOB group on the fiber surface. Then glycopolymer with mannopyranoside as pendent group interacted with the PAA via dynamic covalent bond between sugar and BOB. By combining the results from 2D 1H NMR spectroscopy, the exact binding mode of mannopyranoside pendent group and BOB, i.e., mannopyranoside participated by its diol on 2,3-position instead of that on 4,6-positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In a recent study, a peptide amphiphile with a benzoboroxole (BOB) group attached at the hydrophilic end was assembled into fibers, leading to aligned BOB/saccharide pairs with low molecular mobility, high density and multivalent effect. 141 Thus, enhanced nuclear Overhauser effects could be observed by NMR (NOESY), confirming the binding between BOB and mannopyranoside on the site of diols at 2,3-position instead of 4,6-position.…”
Section: Recognition Of Biologically Active Compoundsmentioning
confidence: 66%
“…In a recent study, a peptide amphiphile with a benzoboroxole (BOB) group attached at the hydrophilic end was assembled into fibers, leading to aligned BOB/saccharide pairs with low molecular mobility, high density and multivalent effect. 141 Thus, enhanced nuclear Overhauser effects could be observed by NMR (NOESY), confirming the binding between BOB and mannopyranoside on the site of diols at 2,3-position instead of 4,6-position.…”
Section: Recognition Of Biologically Active Compoundsmentioning
confidence: 66%
“…Benzoxaborole has been shown by Hall and co-workers to have a strong binding affinity to cis -1,2/1,3-diols of saccharides under physiological conditions. , Therefore, complexation between galactose groups of PLDL and benzoxaborole groups of PAB can lead to cross-linking and subsequent hydrogel formation. To prepare the hydrogels, PLDL and PAB polymers were separately dissolved in PBS, followed by mixing with pipetting.…”
Section: Resultsmentioning
confidence: 99%
“…150 endows these viruses with rich liquid crystal phases. Recent works have also demonstrated that such rodlike viruses are valuable candidates as the backbone for multiple responsive hydrogels. , In the current work, a phenylboronic acid (PBA) derivative ( 1 in Scheme ) with a p K a that is close to the physiological pH was tailor-synthesized and coupled to the nanofibrous M13 virus, leading to fibrous bioconjugates of the PBA-M13 virus that can form dynamic covalent bonds with 1,2 or 1,3 diol-containing agents at physiological pH . Dynamic hydrogels are instantly formed upon mixing poly­(vinyl alcohol) (PVA) and PBA-M13 at the physiological pH, due to binding of the multiple diols of the linear PVA chain with several viruses that cross-link the virus backbone into a three-dimensional network. , The mechanical strength can be tuned by the amount of each component. Excellent injectability and self-healing properties were demonstrated with the current gels.…”
Section: Introductionmentioning
confidence: 98%